Las bases generales de los bienes municipales en el Derecho Administrativo Peruano - Vignolo Cueva, Orlando (2019)
The present publication seeks to develop and explain the different law sources applicableto Peruvian municipal property, considering its conceptual autonomy andspecificity in relation to other public property and the system components diversity(including all sorts of legislative sources and territorial scope, constitutional case lawand specially diverse municipal regulation). This publication intends to achieve aminimum systematic order, which helps to develop legal solutions on day-to day cases,considering the present is disordered and difficult law specialty.